A case report on juvenile ossifying fibroma of the mandible - Mubeen Khan; Vijayalakshmi Kondajji Ramachandra; Preeti Rajguru (Wolters Kluwer Medknow Publications, 2014)
Juvenile ossifying fibroma is considered a unique entity occurring primarily in children and adolescents. Although a benign neoplasm of bone origin, it is an aggressive variant of ossifying fibroma of the jaws. On account of the variable clinical behavior, a highly aggressive nature, and a high tendency for recurrence, early detection and prompt treatment is required. This report presents a case of juvenile ossifying fibroma in an eight-year-old girl, who reported to our institution with a gradually progressive swelling on the left side of her face since nine months, with typical clinical, radiological, and histopathological features.